Cooperative learning technique for teaching general science at ECE level: An experimental study - Hafiza Gulnaz Fatima,; Hina Akbar,; Ibtasam Thakur, (JECCE, 2023)
The goal of the research was to create cooperative learning strategies for young ECE students to accelerate their learning. A pretest and posttest design was used for this study. All ECE students in Punjab Province were the population of the research. From three distinct schools, 120 first-graders were chosen, with 40 from each school were containing the research sample. Three types of research —rural, suburban, and urban—were chosen for the schools using the random sample technique. Experimental group were taught through cooperative learning while the control group received instruction using the conventional approach. All the groups, both experimental and control, pre- and post-testing. The study discovered that cooperative learning has an important impact on students' academic progress. The study has implications for the application of cooperative learning techniques to improve the academic performance of first-graders.